Effects of garlic extract on growth, carcass characteristics and haematological parameters in broilers (Bangladesh Veterinarian, 2016)
Garlic (Allium sativum) is a popular spice in Bangladesh. Its beneficial effect as growth promoter in poultry has not been studied. Broilers were grouped into four: T1 (1% garlic), T2 (2% garlic), Pc (ciprofloxacin positive control) and Nc (negative control). Aqueous extract of garlic (1% and 2%) was administered with drinking water. T1 group (1%) showed better performance with regard to body weight gain than T2 (2%), positive and negative control. In T1 group, significant difference was observed in terms of live body weight gain and dressed weight but no significant differences in feed conversion ratio, offals weight and in blood parameters. It is suggested that 1% aqueous extraction of garlic improves growth and carcass qualities in Broilers.Bangl. vet. 2015. Vol. 32, No. 1, 1-6